FEDERAL DEBT AND THE LACK OF COOPERATION BETWEEN THE BRAZILIAN TREASURY AND CENTRAL BANK BETWEEN 2004 AND 2016 - Marques Vieira Filho, Luiz Alberto; Rossi, Pedro (Brazilian Keynesian Review, 2023)
This article seeks to analyze the relation between fiscal and monetary policy, or, in institutional terms, the relation between the National Treasury and the Central Bank. The underlying hypothesis is that the current relationship between the Brazilian Central Bank and the National Treasury lacks synergy, making more difficult for the government to obtain the desired public debt profile during the years from 2004 to 2016. It will be shown that the Treasury´s intent for better debt profile was opposite by repurchase agreements issued by Central Bank of Brazil. It will be argued that the competition of those repos to government bonds implies a difficulty in the strategy of pre-fixing and lengthening the public debt.